A multi-slotted antenna for LTE/5G Sub-6 GHz wireless communication applications. Issue 5 (29th June 2021) - Azim, Rezaul; Meaze, AKM Moinul H.; Affandi, Adnan; Alam, Md Mottahir; Aktar, Rumi; Mia, Md S.; Alam, Touhidul; Samsuzzaman, Md; Islam, Mohammad T.
Abstract: This paper presents a low-profile multi-slotted patch antenna for long term evolution (LTE) and fifth-generation (5G) communication applications. The studied antenna comprised of a stepped patch and a ground plane. To attain the required operating band, three slots have been inserted within the patch. The insertion of the slots enhances the capacitive effect and helps the prototype antenna to achieve an operating band ranging from 3.15 to 5.55 GHz ( S 11 ≤−10 dB), covering the N77/N78/N79 for sub-6 GHz 5G wireless communications and LTE bands of 22/42/43/46. The wideband antenna presented in this paper offers omnidirectional stable radiation patterns, good gains, and efficiency with a compact size which make this design an ideal contender for wireless fidelity (WiFi), wireless local area network (WLAN), LTE, and sub-6 GHz 5G communication applications.